1996
DOI: 10.1111/j.1476-5381.1996.tb16063.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of the effects of (+)‐PD 128907 on midbrain dopamine neurones in rat brain slices by a selective D2 receptor antagonist L‐741,626

Abstract: 3 (+)-PD 128907 inhibited cell firing in both the ventral tegmental area and substantia nigra pars compacta with EC50 values of 33 nM (pEC5o= 7.48+0.10, n = 10) and 38 nM (pEC50= 7.42+0.15, n = 5), respectively. No effects of (+)-PD 128907 (100 nM) were observed on glutamate or GABA-mediated synaptic potentials elicited by focal bipolar stimulation. 4 L-741,626 antagonized these effects of (+ )-PD 128907 in a concentration-dependent and surmountable manner with an affinity, determined from Schild analysis, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…In contrast, D2 dopamine receptor-preferring antagonist L-741626 (D2/D3 selectivity ratio ϳ10-fold; Bowery et al, 1996) readily antagonizes effects of both LY-341495 (present study) and amphetamine (Millan et al, 2000). Furthermore, lithium chloride, a moodstabilizing agent, reverses a number of behavioral effects of amphetamine, including hyperlocomotion and acoustic star- jpet.aspetjournals.org tle prepulse inhibition deficits (Ong et al, 2005), and, in the present study, it was found to attenuate delayed hyperactivity in LY-341495-treated subjects.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, D2 dopamine receptor-preferring antagonist L-741626 (D2/D3 selectivity ratio ϳ10-fold; Bowery et al, 1996) readily antagonizes effects of both LY-341495 (present study) and amphetamine (Millan et al, 2000). Furthermore, lithium chloride, a moodstabilizing agent, reverses a number of behavioral effects of amphetamine, including hyperlocomotion and acoustic star- jpet.aspetjournals.org tle prepulse inhibition deficits (Ong et al, 2005), and, in the present study, it was found to attenuate delayed hyperactivity in LY-341495-treated subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Given the receptor population reported to be present in the IC, these results strongly suggest that DA-mediated enhancement of coupling is initiated via the D× receptor. The functional consequences of postsynaptic or somatic D× receptor activation in situ have not previously been defined, there being a doubt about the specificity of available compounds used to analyse dopaminergic effects on D× receptors in the ventral tegmental area of the midbrain (Bowery et al 1996). Mitogenesis, c-Fos production, reduction of adenylyl cyclase activity and inhibition of calcium currents have all been variously described as a consequence of agonist activation in a number of cell lines forced to express the D× receptors (see .…”
Section: The Pharmacology Of Dopaminergic Responses In the Islands Ofmentioning
confidence: 99%
“…All drugs demonstrated low nanomolar affinity for their respective receptors (Bowery et al, 1996;Merchant et al, 1996;Audinot et al, 1998) and were administered at 1 mg/kg (into lateral tail vein) before determining the number of spontaneously active DA neurons encountered while making six to nine vertical passes, separated by 200 m, in a predetermined pattern to sample equivalent regions of the VTA. Once a stable dopamine neuron was identified, baseline neuronal activity was recorded for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of selective ligands on the activity of the population of dopamine neurons in the VTA was determined by administering either a selective D2 [3-(4-(4-chlorophenyl-4-hydroxypiperidino)methyl)indole (L-741,626) (Bowery et al, 1996) (Audinot et al, 1998)], or D4 [sonepiprazole (Merchant et al, 1996)] antagonist or vehicle [either acidified (0.1% acetic acid) distilled water (D2) or acidified (0.1% acetic acid) 10% dimethyl sulfoxide in distilled water (D3 and D4)]. All drugs demonstrated low nanomolar affinity for their respective receptors (Bowery et al, 1996;Merchant et al, 1996;Audinot et al, 1998) and were administered at 1 mg/kg (into lateral tail vein) before determining the number of spontaneously active DA neurons encountered while making six to nine vertical passes, separated by 200 m, in a predetermined pattern to sample equivalent regions of the VTA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation